Synopsis of Prosierola (Hymenoptera: Bethylidae) - Azevedo, Celso O. (Zootaxa, 2008)
The identity of many species of Prosierola is currently unknown, mostly because the available taxonomic information is not sufficiently accurate to allow for precise identifications. To solve this problem, nine valid species were investigated. Neotropical species of Bethylinae were also examined in order to find possible misclassified species of Prosierola. In this paper six nomenclatural changes are made, and six valid species recognized. The lectotype of Parasierola flavicoxis Kieffer is designated. The following new species-group synonyms are established: Prosierola lata (Cameron) syn. nov. for Prosierola nasalis (Westwood); Prosierola insularis Evans syn. nov. for Prosierola cubana Evans, and Prosierola bicarinata (Brues) syn. nov. for Prosierola flavicoxis (Kieffer), and Prosierola variegata Evans syn. nov. for Prosierola obliqua Evans. The following new combination is established: Prosierola flavicoxis (Kieffer) from Goniozus.